Pilot Study of Pharyngoesophageal Dysmotility Mechanisms in Dysphagic Infants of Diabetic Mothers - Malkar, Manish B.; Viswanathan, Sreekanth K.; Jadcherla, Sudarshan R. (American Journal of Perinatology, 2019)
Objective Swallowing difficulties are common in infants of diabetic mothers (IDM) and mechanisms are unclear. We tested the hypothesis that pharyngoesophageal motility reflexes are distinct in IDMs compared with healthy controls in a pilot study.Study Design Basal and adaptive pharyngoesophageal motility characteristics of 20 dysphagic IDMs and 10 controls were studied using purpose-built micromanometry system.Results During basal swallows, IDMs had lower frequency of deglutition apneas (62.5 vs. 95.4%) and longer active upper esophageal sphincter (UES) relaxation duration (0.8 ± 0.1 vs. 0.4 ± 0.1 second), whereas during adaptive swallows, IDMs had longer response latency to esophageal peristalsis onset (24.4 ± 2.1 vs. 9.7 ± 2.9 seconds) and longer lower esophageal sphincter nadir duration (28.9 ± 3.2 vs. 12.9 ± 4.6) (all p < 0.05) compared with controls. Nine in the IDM group needed gastrostomy feeding tube at hospital discharge versus none in controls.Conclusion Feeding difficulties in IDMs are likely to be associated with maladapted or maldeveloped vagal neuropathy mechanisms manifesting as dysregulation of pharyngeal–airway interactions, longer active UES relaxation response, delays in the activation of esophageal contractile apparatus during peristalsis, and prolonged inhibition at the gastroesophageal junction.
Keywords: infants of diabetic mothers; esophageal motility; dysphagia